Encapsulation of Polygonum bistorta root phenolic compounds as a novel phytobiotic and its protective effects in the mouse model of enteropathogenic Escherichia coli infection - Zahra kadkhoda Mezerji; Reza Boshrouyeh; Seyedehfarnaz Hafezian Razavi; Shaghayegh Ghajari; Hasti Hajiha; Negin Shafaei; Ehsan Karimi; Ehsan Oskoueian (BMC, 2023)
Abstract Background Microencapsulation technology is the fundamental delivery system for encapsulating the natural bioactive compounds especially phenolic in order to developing bioavailability, stability and controlling release. This study was conducted to determine the antibacterial and health-promoting potential of the phenolic rich extract (PRE)-loaded microcapsules obtained from Polygonum bistorta root as a dietary phytobiotic in mice challenged by enteropathogenic Escherichia coli (E. coli). Method The PRE was obtained from Polygonum bistorta root using fractionation by different polarity solvents and the highest PRE was encapsulated by the combination of modified starch, maltodextrin, and whey protein concentrate as wall materials using a spray dryer. Then, the physicochemical characterization (particle size, zeta potential, Morphology and polydispersity index) of microcapsules have been assessed. For the invivo study, 30 mice at five treatment were designed and antibacterial properties were analyzed. Furthermore, relative fold changes in the ileum population of E. coli was investigated using Real time PCR. Results The encapsulation of PRE resulted in the production of phenolic enriched extract-loaded microcapsules (PRE-LM) with a mean diameter of 330 nm and relatively high entrapment efficiency (87.2% w/v). The dietary supplementation of PRE-LM improved weight gain, liver enzymes, gene expression, morphometric characteristics of the ileum and decreased the population of E. coli present in the ileum significantly (p < 0.05). Conclusion Our funding suggested PRE-LM as a promising phytobiotic against E. coli infection in mice.